Reactivation of cytomegalovirus, human herpes virus, and Epstein-Barr virus infections after hemapoietic stem cell transplantation in children - T. V. Antonova; O. E. Pobegalova; O. V. Gorchakova; L. S. Zubarovskaya; O. S. Yudinceva; D. A. Lioznov (Журнал инфектологии)
Study objective: to evaluate frequency of CMV, HHV-6, and EBV reactivation in children within 60 days after HSCT.Materials and methods: The study was carried out in Raisa Gorbacheva Memorial Research Institute for Pediatric Oncology, Hematology, and Transplantation of the Pavlov First Saint Petersburg State Medical University We analyzed 95 medical records of pediatric patients who underwent HSCT in 2021. Pretransplant serostatus for CMV, EBV, HHV-6 was studied, as well as the frequency and timing of virus reactivation after transplantation. In the prospective part, 35 children aged from 1 to 17 years were enrolled. The pretransplant evaluation included detection of anti-CMV, anti-HHV-6, and anti-EBV IgM and IgG by ELISA, and blood PCR for viremia. DNA of herpes viruses was identified by quantitative blood PCR on the day of HSCT, and then 10, 20, 30 and 60 days after HSCT. The number of viral DNA copies was calculated per 105 cells. Statistical analysis was carried out using SPSS Statistics 22 software package.Results: On pre-transplant evaluation, 47 of 95 pediatric patients were tested for CMV with positive result in 36 children, 27 patients were tested for EBV and 17 were positive. HHV-6 DNA was detected in 3 of 25 patientsMostly, reactivation of herpes viruses occurred in the early period up to 60 days. HHV-6 reactivation was observed on average 25±4 days after transplantation, significantly earlier than for CMV and EBV.In a prospective study, reactivation of CMV, HHV-6, and EBV was revealed in 28 (80%) patients within 60 days of transplantation, with a maximum number of patients in 20 days after HSCT.A trend toward an increase in CMV and HHV-6 concentration in blood was observed on days 10 and 20 after HSCT, with a maximum viral load of HHV-6 and minimal EBV replicative activity. Clinically significant manifestations of herpesvirus infection were diagnosed in 19 (54.3%) patients.Conclusion: High seropositivity for CMV and EBV was revealed in children before transplantation. Herpes viruses reactivation occurs early in post-transplant period, on the 20th day after HSCT, HHV-6 in forms of mono- and mixed infection predominates with a trend toward increasing viral load.